We know that
in the triangle TQS
<span>applying the Pythagorean theorem
QS</span>²=TS²+TQ²---------> TQ²=QS²-TS²--------> TQ²=18²-9x²-----> equation 1
in the triangle TRS
TS²=TR²+RS²--------------> TR²=TS²-RS²-------> TR²=9x²-144----> equation 2
in the triangle QTR
TQ²=TR²+36-----------> equation 3
<span>I substitute 1 and 2 in 3
</span>18²-9x²=9x²-144+36--------> 18x²-432=0------> x²=24-------> x=√24
x=2√6
TS=3*x------> 3*2√6-----> 6√6
TS=6√6 units
the answer is
TS=6√6 units
<span>6 is the square root of 6 units</span>
did you ever get the answer?
Answer:
Ok, we know that we can write a horizontal translation as:
y' = f(x - A)
where if A is positive, this moves the graph of f(x) A units to the right.
Why is this?
Ok, let's compare:
y = f(x)
and
y' = f(x - A)
in y, when x = 0 we have f(0).
While to have this same point in y', we need to evaluate in x = A.
f(A - A) = f(0).
Then the value f(0) is now at x = A, this means that the point moved A units to the right.
And you can do this for all the values, so you will find that the entire graph of f(x) has ben moved A units to the right.
Answer:
6x²5y²6 cm²
Step-by-step explanation:
(2xy3) x (4x5y6)
(2x) x (4x) = 6x²
(y) x (5y) =5y²
6x²5y²6 cm²
Step-by-step explanation:
I wrote the steps in different colour pen so that it would be easier
Hope this is correct and helpful
HAVE A GOOD DAY!